GLOBAL SUPPLY CHAIN RISK MANAGEMENT - Manuj, Ila; Mentzer, John T. (Journal of business logistics, 2008)
Global supply chains face a multitude of risks. A review of the recent literature reveals a few structured and systematic approaches for assessing risks in supply chains. However, there is no conceptual framework that ties together this literature. The purpose of this paper is to integrate literature from several disciplines ‐ including logistics, supply chain management, operations management, strategy, and international business ‐ to develop a model of global supply chain risk management. The implications for stakeholders and how future research could bring more insights to the phenomenon of global supply chain risk management are also discussed.